Imaging of Alimentary Tract Perforation - Romano, Luigia; Pinto, Antonio (Springer International Publishing : Imprint: Springer, 2015)
This book provides an overview on the critical role of diagnostic imaging in the assessment of patients with suspected alimentary tract perforation, an emergent condition that requires prompt surgery. With the aid of numerous high-quality images, it is described how different imaging modalities, including plain film X-ray, ultrasonography, and multidetector row computed tomography (MDCT), permit correct diagnosis of the presence and cause of the perforation and of associated pathologies. Particular attention is paid to MDCT, with full description of its role in a range of scenarios at various levels of the alimentary tract. Imaging of GI tract perforation in different patient groups, such as pediatric patients, the elderly, and oncologic patients, is also addressed. This volume will greatly assist residents in radiology, radiologists, and physicians who are daily involved in the management of patients with clinically suspected alimentary tract perforation.